2022
DOI: 10.1108/ijchm-04-2022-0419
|View full text |Cite
|
Sign up to set email alerts
|

Beyond competing for talent: an integrative framework for coopetition in talent management in SMEs

Abstract: Purpose This paper aims to unpack how small and medium-sized enterprises (SMEs) can operationalise coopetition in talent management, addressing ongoing talent shortages in the hospitality industry which were intensified during the Covid-19 pandemic. Design/methodology/approach This conceptual paper draws from literature on coopetition and talent management in SMEs. Specifically, the authors take an interorganisational talent pool lens and develop a framework following the principles of open-systems theory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 80 publications
0
31
0
1
Order By: Relevance
“…The criteria to select talent respondents were guided by the literature on talent management and by the recommendation of the head of HR or the heads of talent management. Consistent with talent management literature, the study used the following criteria: (a) being a manager or employee with high potential and high performing; (While specific definitions depend on organisational contexts, a strong focus is placed on high performers and/or high potentials); (b) having at least 12 months of experience in the organization, and (c) being retained during the COVID-19 pandemic period consistent with the study context to examine the relationships of response strategies with talent retention ( Collings and Mellahi, 2009 ; Jooss et al, 2019 , 2022 ; Kravariti, et al, 2022 ; Mai and Thuy 2021 ; Tansley, et al, 2007 ; Zhang et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The criteria to select talent respondents were guided by the literature on talent management and by the recommendation of the head of HR or the heads of talent management. Consistent with talent management literature, the study used the following criteria: (a) being a manager or employee with high potential and high performing; (While specific definitions depend on organisational contexts, a strong focus is placed on high performers and/or high potentials); (b) having at least 12 months of experience in the organization, and (c) being retained during the COVID-19 pandemic period consistent with the study context to examine the relationships of response strategies with talent retention ( Collings and Mellahi, 2009 ; Jooss et al, 2019 , 2022 ; Kravariti, et al, 2022 ; Mai and Thuy 2021 ; Tansley, et al, 2007 ; Zhang et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Both the talent management and hospitality literature reveal a lack of clarity, conceptualisation and theorisation, along with a significant lack of empirical evidence with regard to the talent definition and identification processes (criteria) ( Jooss, et al, 2019 , 2022 ; Kravariti, et al, 2022 ). It also found that talents differ to an extent across the various hospitality and tourism sectors and countries, suggesting that talent’s operationalisation is context-dependent.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations